Some problems of investigating street fraud and the ways to solve them - K. D. Zaiats (Law and Safety)
The subjects of the study are the problems that arise at the initial stage of the investigation of street fraud, the study is the individual problems of pre-trial investigation of street fraud and the ways of their solution. The study aims to highlight the most common problems in practice at the initial stage of the investigation of this group of fraud, and presents recommendations for their solution.